The Impact Of Financial Management Skills, Financial Satisfaction, And Future Planning On Savings Levels - Novita, Wellia; Edriani, Devi; Kusnara, Hasti Pramesti (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This article investigates the nexus of financial management skills, financial satisfaction, and future planning as determinants of savings levels among individuals in Bank Indonesia West Sumatra. Employing a multiple linear regression analysis with a sample of 45 participants and utilizing SPSS for data analysis, the study reveals compelling insights. Results indicate that higher financial management skills, increased financial satisfaction, and effective future planning positively correlate with elevated savings levels. The model, supported by robust F-square and R-square values, signifies its statistical significance and explanatory strength. These findings underscore the pivotal role of financial literacy, contentment, and proactive planning in shaping individuals' financial behaviors and, consequently, their savings levels. The implications extend to both personal financial decision-making and regional economic policies, emphasizing the need for targeted initiatives to enhance financial well-being in Bank Indonesia West Sumatra.